(untitled) (Web of Teachers: Inderscience Research, 2025)
If we talk about children, then for them financial literacy is an understanding of economic processes and the formation of the right attitude towards money in the future. The purpose of the article is to develop and test a lesson on financial literacy for younger students. As a result of the study, it was found that schoolchildren show a high interest in the topic of the lesson, they are actively working, but they know very little about finance, which actualizes systematic work on teaching financial literacy among schoolchildren.